Effect of home based pulmonary rehabilitation on health related quality of life in COPD patients - Mathew, John; Balakrishnan, Jayaprakash; Nair, Sanjeev (International Journal of Research in Medical Sciences, 2018)
Background: Pulmonary rehabilitation is a proven strategy in the management of COPD, it’s a neglected area in our part of world and there are very few studies on home based pulmonary rehabilitation in COPD in our scenario and hence we evaluated the effectiveness of such a strategy. Aim of the research work was to study the effectiveness of home based pulmonary rehabilitation on health related quality of life, exercise tolerance, depression levels and perceived dyspnea as assessed by SGRQ (St. George Respiratory Questionnaire), 6MWTD (Six-Minute Walk Test distance), PHQ-9 (Patient Health Questionnaire-9), Modified Borg scale respectively. Methods: Patients attending the Department of Pulmonary Medicine, Medical College Trivandrum, diagnosed as COPD based on GOLD guidelines who fulfil the inclusion and exclusion criteria were studied from January 2013 to June 2014. Patients were educated about the disease and need for rehabilitation, advised smoking cessation, nutritional modification. Breathing exercise, upper limb and lower limb exercises given for 6 weeks in a structured manner and followed up in every second week and analyzed using paired t- test. Pre and post rehabilitation assessment included the SGRQ, 6MWTD, PHQ-9, Modified Borg dyspnea scale was done. Results: Around 40 patients had completed 6weeks of rehabilitation. There was a statistically and clinically significant improvement in quality of life, exercise tolerance, perceived dyspnoea was seen along with decrease in level of depression. Conclusions: Home based pulmonary rehabilitation is a feasible alternative to institution based rehabilitation in the management of COPD and is associated with significant benefit.